Analysis and Evaluation of the Countermeasures for the Protection Measures of Subway Near-line Pipeline. Issue 1 (January 2020) - Xu, Weiping; Zhao, Chuxuan; Hou, Zonghao; Yuan, Ziyi; Xiao, Zhifei; Sun, Keguo
Abstract: With the rapid development of urban rail transit, engineering cases such as subway proximity pipelines are not uncommon, and it is increasingly important to take corresponding measures to protect existing pipelines. In this paper, the numerical simulation method is used to study the effect of protective measures on an underground pipeline. It is found that: (1) The maximum tensile and compressive stresses of the underground pipelines when they are not applied as protective structures are 0.719 MPa and 1.319 MPa, respectively. The maximum tensile and compressive stresses are located at the top and both sides of the pipeline; (2) the pipeline is not protected. The maximum vertical displacement of the structure is below the frame bridge, which is 2.42mm, which is less than the displacement control amount of 10mm. (3) The simultaneous protection structure and the sand pebble replacement layer have the largest reduction of stress and deformation, among which the stress The effect of controlling the replacement layer is better than that of the protective structure, and the control effect for the deformation is similar. The research results can provide theoretical support for the selection of underground pipeline protection measures, with technical guidance and reference.